2012
DOI: 10.1523/jneurosci.1742-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Pain Intensity the First Year after Lumbar Disc Herniation Is Associated with the A118G Polymorphism in the Opioid Receptor Mu 1 Gene: Evidence of a Sex and Genotype Interaction

Abstract: Earlier studies have shown that the single nucleotide polymorphism (SNP) A118G (rs1799971) in the opioid receptor mu 1 (OPRM1) gene may affect pain sensitivity. In the present study we investigated whether the A118G SNP could predict clinical outcome regarding progression of pain intensity and disability in patients with low back pain and sciatica after lumbar disc herniation. Patients (n ϭ 258) with lumbar disc herniation and sciatic pain, all European-Caucasian, were recruited from two hospitals in Norway. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 32 publications
1
67
1
Order By: Relevance
“…Regarding COMT , polymorphisms and haplotypes have been associated with laboratory pain sensitivity, and acute and chronic clinical pain [13,40], including long-term outcomes after back surgery [143]. Similarly, the A118G polymorphism of OPRM1 has been associated with experimental pain sensitivity and with clinical pain [53,71,123], including long-term outcomes of acute back pain [124]. Finally, GCH1 genotypes have been associated with experimental and clinical pain responses across several cohorts [15,28,159,160], and GCH1 genotypes have predicted outcomes from lumbar spine surgery [96,160].…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding COMT , polymorphisms and haplotypes have been associated with laboratory pain sensitivity, and acute and chronic clinical pain [13,40], including long-term outcomes after back surgery [143]. Similarly, the A118G polymorphism of OPRM1 has been associated with experimental pain sensitivity and with clinical pain [53,71,123], including long-term outcomes of acute back pain [124]. Finally, GCH1 genotypes have been associated with experimental and clinical pain responses across several cohorts [15,28,159,160], and GCH1 genotypes have predicted outcomes from lumbar spine surgery [96,160].…”
Section: General Considerationsmentioning
confidence: 99%
“…For example, previous studies have reported that COMT, OPRM1 , and GCH1 show sex-specific associations with pain responses [14,15,124]. In addition, COMT haplotypes have been shown to interact with psychological functioning (i.e., pain catastrophizing) to predict both experimental and clinical shoulder pain outcomes [58,60].…”
Section: General Considerationsmentioning
confidence: 99%
“…In a twin study of low back pain comparing 2108 mono-and dizygotic twins suggested that a small genetic contributor might play a role in men but not in women. A study of 258 patients with lumbar disc herniation suggested that the A118G gene might play a role in postoperative pain [24].…”
Section: Expert Point Of Viewsmentioning
confidence: 99%
“…[11] Moreover, a recent study in patients with low back pain and sciatica after lumbar disc herniation found that this same allele increased twice the pain intensity in women compared to men. [12] Thus, human pain genes may have sex-biased effects affecting both sexes but to different degrees; sex-specific effects affecting only one but not another sex; and sex-antagonistic effects affecting both sexes but in opposite directions.…”
Section: öZetmentioning
confidence: 99%